What young india wants : selected essays and columns - Bhagat, Chetan (New Delhi : Rupa, 2015)
In his latest book, What young India wants, Chetan Bhagat asks hard questions, demands answers and presents solutions for a better, more prosperous India. Aout the book Why do our students regularly commit suicide? Why is there so much corruption in India? Can't our political parties ever work together? Does our vote make any difference at all? We love our India, but shouldn t some things be different? All of us have asked these questions at some time or the other. So does Chetan Bhagat, India's most loved writer, in What young India wants, his first book of non-fiction. What young India wants is based on Chetan Bhagat's vast experience as a very successful writer and motivational speaker. In clear, simple prose, and with great insight, he analyses some of the complex issues facing modern India, offers solutions and invites discussion on them. And, at the end, he asks this important question: Unless we are all in agreement on what it is going to take to make our country better, how will things ever change? If you want to understand contemporary India, the problems that face it, and want to be a part of the solution, What young India wants is the book for you."--
Keywords: India -- Social conditions -- 21st century; Education -- India; India -- Politics and government -- 21st century